Genomic Signatures Supporting the Symbiosis and Formation of Chitinous Tube in the Deep-Sea Tubeworm Paraescarpia echinospica. (13th July 2021) - Sun, Yanan; Sun, Jin; Yang, Yi; Lan, Yi; Ip, Jack Chi-Ho; Wong, Wai Chuen; Kwan, Yick Hang; Zhang, Yanjie; Han, Zhuang; Qiu, Jian-Wen; Qian, Pei-Yuan
Abstract: Vestimentiferan tubeworms are iconic animals that present as large habitat-forming chitinized tube bushes in deep-sea chemosynthetic ecosystems. They are gutless and depend entirely on their endosymbiotic sulfide-oxidizing chemoautotrophic bacteria for nutrition. Information on the genomes of several siboglinid endosymbionts has improved our understanding of their nutritional supplies. However, the interactions between tubeworms and their endosymbionts remain largely unclear due to a paucity of host genomes. Here, we report the chromosome-level genome of the vestimentiferan tubeworm Paraescarpia echinospica . We found that the genome has been remodeled to facilitate symbiosis through the expansion of gene families related to substrate transfer and innate immunity, suppression of apoptosis, regulation of lysosomal digestion, and protection against oxidative stress. Furthermore, the genome encodes a programmed cell death pathway that potentially controls the endosymbiont population. Our integrated genomic, transcriptomic, and proteomic analyses uncovered matrix proteins required for the formation of the chitinous tube and revealed gene family expansion and co-option as evolutionary mechanisms driving the acquisition of this unique supporting structure for deep-sea tubeworms. Overall, our study provides novel insights into the host's support system that has enabled tubeworms to establish symbiosis, thrive in deep-sea hot vents and cold seeps, and produce the unique chitinous tubes in the deep sea.